أصول نظرية النقد النحوي لدى أبي حيان الأندلسي(دراسة تطبيقية على تفسير البحر المحيط): The ideological Principles of critical analysis of Abū Ḥayyān Athīr ad-Dīn al-Gharnāṭī (Adaptive Research on Tafsir Al Bahr Al Muhit) - Dr. Abdul Saboor Fakhiri, (MEI, 2023)
The Noble Qur’an played an important role in the formation of Arabic grammar and enacting its laws, and grammar on the other hand played a prominent role in the interpretation of the Holy Qur’an, uncovering its secrets, and showing its protectionism and its merits. The necessity and the great and serious interest in grammar appeared on the part of linguists and grammarians because of corruption in the language of the people of Arabic and the spread of melody in the tongues of the speakers of the language of Dhad as a result of the mixing of Arabs with non-Arabs in living, intermarriage, trade, or anything else. Muslim scholars feared for the Arabic language to be lost and for the Noble Qur’an from misunderstanding and distortion, as happened in the previous divine books. So they began to collect the language through the different trips between the Arab tribes, listen to the sayings of the pure Arabs, memorize their poems, and then set the rules according to those audios.